The Dynamics of Religiosity among Members of Muslim Minorities in Purbo Jolotigo Talun of Pekalongan Central Java - Esti Zaduqisti; Ali Mashuri; Purnomo Rozak (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This study examines the dynamics of religious awareness, religious experience, religious maturity, religious conversion, and the factors influencing religiosity among Muslim minorities in Purbo, Pekalongan, Central Java, Indonesia. A qualitative descriptive research approach was employed, with informants selected through a snowball sampling technique. The findings reveal several key insights. First, the religious awareness of Muslim minorities in Purbo Hamlet is characterized by a profound sense of faith, which is perceived as a divine gift from Allah (SWT). However, their religious experience is primarily centered on ritual worship, viewed more as an obligatory practice than as a deeply transformative spiritual engagement. Second, religious maturity among the Muslim minority does not fully align with established theoretical criteria, exhibiting distinct characteristics that differentiate it from conventional models. Third, religious conversion occurs in two directions: conversion to Islam and conversion away from Islam, with marriage being the predominant driver of religious shifts. Fourth, the dynamics of religiosity among Muslim minorities in Purbo are shaped by both internal and external factors, including developmental age, subjective religious experiences, education, environmental influences, and cultural norms. These findings contribute to a deeper understanding of the complexities surrounding religious identity within minority communities.